1977
DOI: 10.1002/ana.410010217
|View full text |Cite
|
Sign up to set email alerts
|

An immunological and cytogenetic investigation of tuberous sclerosis

Abstract: Patients with tuberous sclerosis werestudied to investigate t h e pathophysiological basis for hamartoma and neoplasia development in this disease. Chromosome banding, aberration following G-2 x-ray exposure, and the frequency of sister chromatid exchange were normal. Mean IgM levels were significantly elevated above those of random institutionalized control patients b u t not above cottage-mate controls. Although 4 out of 10 patients did not respond to any of the skin test antigens used, tuberous sclerosis pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In accord with the findings of Roos (1977), the present study showed that the baseline SCE frequencies in the peripheral blood lymphocytes from TS patients are in the normal range. We (1985) reported that there were no significant differences in the SCE frequencies between the lymphocytes from TS patients and those from normal controls exposed to various doses of MMC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accord with the findings of Roos (1977), the present study showed that the baseline SCE frequencies in the peripheral blood lymphocytes from TS patients are in the normal range. We (1985) reported that there were no significant differences in the SCE frequencies between the lymphocytes from TS patients and those from normal controls exposed to various doses of MMC.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there are some reports indicating that fibroblasts and lymphocytcs from TS patients are hypersensitive to gamma-ray and N-methyl-N'-nitro-N-nitrosoguanidine (Scudiero et al, 1981;Paterson et al, 1982). Roos (1977) reported that the frequencies of spontaneous SCEs in cells from TS patients were normal and we reported that the SCE response to mitomycin C (MMC) was also within the normal range (Iijima et al, 1985). However, there are no reports about radiation induced chromosome aberrations and SCEs in lymphocytes from TS patients.…”
Section: Introductionmentioning
confidence: 87%
“…In a cytogenetical study of TS lymphocytes, Suzuki (1977) showed increased frequencies of spontaneous chromosome aberrations, especially increased chromatid interchanges in the advancedage group. However, Roos et al (1977) reported normal frequencies of chromosome aberrations and SCE in TS lymphocytes following G2 X-ray exposure. Our study failed to reveal cytogenetic abnormalities in TS lumphocytes, and suggested that TS cells have no increased spontaneous or MNNGinduced chromosome instability.…”
Section: Discussionmentioning
confidence: 95%
“…Suzuki (1977) and Roos et al (1977) found no obvious cytogenetic abnormalities in TS, including induced chromosomal aberrations following X-ray or UV irradiations. However Paterson et al (1982) and Scudiero et al (1982) reported that the cells from some TS patients were hypersensitive to the lethal effects of ionizing radiation and N-methyl-N'.nitro-N-nitrosoguanidine (MNNG), respectively.…”
Section: Introductionmentioning
confidence: 97%